10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: Pre-professional dancers train within environments characterised by intense evaluation, perfectionistic norms, and high psychological and physical demands, making the identification of factors that support wellbeing particularly important. This study examined the extent to which internal psychological resources, and perceived peer motivational climate predicted subjective wellbeing in full-time Australian dance students, and whether peer climate mediated these relationships. METHODS: Participants (n = 158; M_age = 18.91) completed validated measures of resilient coping, mental toughness, peer motivational climate, and life satisfaction. RESULTS: Correlational analyses showed that resilient coping and mental toughness were positively associated with subjective wellbeing, supporting hypotheses that internal psychological resources contribute to dancers' wellbeing. Task-involving peer climate demonstrated a small positive association with wellbeing, with relatedness support emerging as the only significant sub-factor. Mediation analyses indicated that neither task- nor ego-involving peer climates mediated the relationships between resilient coping or mental toughness and wellbeing, suggesting these individual resources operate independently of perceived peer environments. Mental toughness was positively associated with perceptions of a task-involving climate, but this did not translate into indirect effects on wellbeing. DISCUSSION: Findings highlight the important role of internal psychological resources in supporting dancers' wellbeing and suggest that while peer climates matter, their influence may be secondary to the individualised and competitive nature of pre-professional dance training. Implications for psychological skills training and supportive pedagogical practices are discussed.